Evolution and Evaluation of Duplex Grain of As-cast 30Cr2Ni4MoV Steel during Heat Treatment - Xiuzhi ZHANG; Zhilong LIU; Jiansheng LIU; Shue DANG (Medžiagotyra)
As the main microstructure flaw of heavy forging, duplex grain (the grain size is non-uniform) may result in producing a reject. In this paper, the influences of heat treatment temperature and isothermal holding time on the duplex grains evolutions of as-cast 30Cr2Ni4MoV steel were studied using optical microscope and scanning electron microscope aided with XRD and EDS. It is shown that the globular austenite grains appear at 750 °C and the austenite grains in the regions rich in C, Cr, Ni, and Mo are smaller than that in other regions. Duplex grains appear in the heating process. Moreover, in the isothermal heat treatment process, grains with different grain size number also developed at all of the temperatures performed in the study. But the distribution of the grains with different sizes cannot be evaluated precisely using proper method commonly used now. On the basis of analysis of the sizes of the duplex grains, a new approach for evaluating the level of the mixture of different size grains was proposed, the result obtained are consistent with the experimental results. The microstructure of 30Cr2Ni4MoV could be more uniform by increasing the temperature and extending the heat-preservation time.